Bibliometric analysis of acute limb ischemia research: Global trends and key insights from 2000-2024 - Abiseka Panji Baskoro; Enrico Ananda Budiono; Heru Sulastomo; An Aldia Asrial (Universitas Brawijaya, 2026)
Background: Acute Limb Ischemia (ALI) remains a critical vascular emergency, necessitating understanding to prevent devastating outcomes. Despite its clinical significance, a comprehensive understanding of global research trends, key contributors, and emerging themes in ALI remains underexplored. Objective: This study aims to perform a bibliometric analysis of ALI-related research, identifying trends, influential contributors, and areas for future exploration. Methods: Data were retrieved from the Scopus database using relevant keywords. Bibliometric metrics were analyzed using VOSviewer and Biblioshiny, focusing on publication trends, co-authorship networks, and keyword co-occurrence. Descriptive and visual analyses highlighted the leading journals, nations, and emerging research themes in ALI. Result: A total of 1,967 documents were identified, with a surge in publications from 2020 to 2021, likely driven by the COVID-19 pandemic's thrombotic implications. The United States led global research efforts with 28.5% of corresponding author articles and the highest citation impact. Annals of Vascular Surgery and Journal of Vascular Surgery emerged as the most relevant and influential journals, respectively. Keyword mapping identified